2020
DOI: 10.1021/acs.jpcc.0c04521
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of the Adsorption and Dissociation of Copper(I) Acetamidinates on Ni(110): The Effect of the Substrate

Abstract: In order to assess the role of metal substrates on the thermal chemistry of adsorbed acetamidinate metalorganic compounds, we have studied the surface chemistry of copper-(I)−N,N′-dimethylacetamidinate on Ni(110) using density functional theory and contrasted it with similar calculations we previously carried out on Cu(110). At low coverages, it was found that, in its most stable configuration, the molecular adsorption of copper(I)−N,N′-dimethylacetamidinate dimers occurs with the Cu atoms occupying surface ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…This indicates that some of the adsorbed Cu-complex may remain in molecular form upon deposition at 450 K, or, perhaps more likely, that they undergo minimal conversion, reversible upon exposure to atomic hydrogen. The most likely explanation is that the dimeric (or tetrameric) form in which these Cu iminopyrrolidinate precursors exist in gas and solid phases is activated on the surface to form monomeric adsorbates. ,,,, Upon exposure to atomic hydrogen, those can desorb as monomers, reversibly recombine to desorb back into the gas phase as dimers, or react to liberate the ligands in hydrogenated/protonated form and to reduce the Cu center.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that some of the adsorbed Cu-complex may remain in molecular form upon deposition at 450 K, or, perhaps more likely, that they undergo minimal conversion, reversible upon exposure to atomic hydrogen. The most likely explanation is that the dimeric (or tetrameric) form in which these Cu iminopyrrolidinate precursors exist in gas and solid phases is activated on the surface to form monomeric adsorbates. ,,,, Upon exposure to atomic hydrogen, those can desorb as monomers, reversibly recombine to desorb back into the gas phase as dimers, or react to liberate the ligands in hydrogenated/protonated form and to reduce the Cu center.…”
Section: Resultsmentioning
confidence: 99%
“…Migration of the remaining ligands from the Ni atoms to the surface most likely occurs in tandem with ligand fractioning. It is interesting to note that ligand migration is in general one of the expected initial steps during the activation of metal organic ALD precursors adsorbed on solid surfaces. ,, What is not clear is if this transition occurs before or after any ligand decomposition. Previous reported quantum mechanics calculations with Cu­(acac) 2 on Cu and Ta surfaces led to the conclusion that stepwise migration of the acac ligands to the surface is facile but on Cu is not followed by any subsequent dissociation reactions. , On the other hand, our experimental studies of Cu­(acac) 2 activation on Cu and Ni surfaces indicated early ligand decomposition on the metal center (via the loss of a terminal methyl group), before migration to the surface.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that ligand migration is in general one of the expected initial steps during the activation of metal organic ALD precursors adsorbed on solid surfaces. 79,124,125 What is not clear is if this transition occurs before or after any ligand decomposition. Previous reported quantum mechanics calculations with Cu(acac) 2 on Cu and Ta surfaces led to the conclusion that stepwise migration of the acac ligands to the surface is facile but on Cu is not followed by any subsequent dissociation reactions.…”
Section: ■ Discussionmentioning
confidence: 99%
“…On the basis of these results, the present research work aims at providing a step forward in the investigation of these issues by combined calculations involving the density functional theory (DFT) coupled with ab initio molecular dynamics (AIMD) [ 25 ]. It is worth noticing that, despite the growing interest in understanding via quantum chemical approaches the microscopic details of molecule-to-material conversion in CVD or ALD processes [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], most literature data refer to geometry optimization or transition state calculations performed at 0 K. Whereas these studies contribute to shedding light on the binding of the metal center with substrate atoms, the formation of metal-surface linkages for the target CVD precursors, where the metal center is completely surrounded by ligands, requires the dissociation of at least one metal-ligand bond, and remains a key issue to be further investigated.…”
Section: Introductionmentioning
confidence: 99%